TOPONIMI SAMBAS - Bambang Hendarta Suta Purwana (Balai Pelestarian Nilai budaya Daerah Istimewa Yogyakarta, 2018)
Using the data from library research, this descriptive qualitative research aims to answer the following questions: (1) What are the historical aspects underlying the establishment of the social structure of Sambas people in the past in relation to the existence of the Dayak and the Malay Sambas communities? (2) How is the social relation between the Dayak and the Malay Sambas communities in the Sambas regency? (3) What is the significance of the toponymy of Sambas for the social life in Sambas regency nowadays.The oath taken by the Dayak and the Malay Sambas is not a fictional story but is a sociological reality that indicates the strength of brotherhood in their daily life. The brotherhood narration of the two ethnic goups in Sambas is always important to discuss in order to keep the collective memory of Sambas society.